If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.26 = logx Solving -0.26 = glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1glox' to each side of the equation. -0.26 + -1glox = glox + -1glox Combine like terms: glox + -1glox = 0 -0.26 + -1glox = 0 Add '0.26' to each side of the equation. -0.26 + 0.26 + -1glox = 0 + 0.26 Combine like terms: -0.26 + 0.26 = 0.00 0.00 + -1glox = 0 + 0.26 -1glox = 0 + 0.26 Combine like terms: 0 + 0.26 = 0.26 -1glox = 0.26 Divide each side by '-1lox'. g = -0.26l-1o-1x-1 Simplifying g = -0.26l-1o-1x-1
| -4(-5-b)= | | 3(x-9)=6(x+3) | | sinx=-0.95 | | 10x+15x-8+3=-2x+3-8 | | 7p-8=-3p+6 | | 2=4y-2y-6 | | 6e-15=15 | | x+37=3x+9 | | (x-8)+23-4=36 | | 42=28-3c | | 5k+26=1 | | -3e^1-x=11 | | (-r^2)+4(-r)-4=-8 | | 6-c=3 | | 7/8x-1/3y=3 | | 7x-6.4-0.1x+3.7x-1= | | q^2-8q+20=0 | | q^2-81+20=0 | | X-4x=-6-3 | | X^2-x+5=41 | | X^2-x+5=3 | | sn=n^2 | | -30.07/-0.02 | | x^2+2xy+y^2-y= | | x^2+2xy+y^2-y=0 | | 6x^2+9=12 | | 0.26-0.02(x+2)=-0.04(2-x) | | 2z/10-9=-8 | | 26-12=2(x-3) | | 10p+13=4p-5 | | 13/6z=-9 | | (D^4+D^3-4D)y=0 |